AB0841 Tendon Involvement in Chronic Tophaceous Gout Detected by Dual-Anergy-Computertomography. (10th June 2014) - Fiene, M.; Karnebeck, V.; Rosenberg, C.; Behrndt, P.O.
Abstract : Background: Gout is the most prevalent metabolic arthritis and affects about 8, 3 million inhabitants in the USA. Epidemiologic data from Europe are comparable and indicate that gouty arthritis or chronic tophaceous gout evolves as a public health problem with raising prevalence. Patients with chronic tophaceous gout have a high cardiovascular risk. Additionally cardiovascular medication, such as acetylsalycilic acid, antihypertensive or diuretics have an influence of renal urate handling which might cause gout attacks. Therefore it is necessary to identify these patients to prevent them from new attacks. Serum measurement of urate levels might not be sufficient for this purpose. Objectives: The dual-energy-computertomography (DECT) is a new method to detect monosodiumurate (MSU) deposits. Using two different x-ray voltages (80 and 140 kV) in combination with Hounsfield-units allows to separate calcium vom sodium and separate MSU from other adjacent structures. Using DECT for tophus detection reveals much more MSU deposits compared to clinical examination. We tried to determine the extent of the involvement of anatomical structures in tophus deposition. Methods: In this study we used DECT to determine bone and tendon involvement of 14 patients with chronic tophaceous gout. There is no established gold standard for DECT evaluation. Therefore DECT-scans were independently assessed by a radiologist and a rheumatologist to determine the extent of bone and tendon involvement of the feet. Tophi were allocated to the involved bone and tendon. Tophussize was rated semiquantitatively (0-5). Results: Our patients do not differ in their demographic data from other published results. There were more men than women affected and the average age is over 60 years old which is in line with other publications. Both examiners revealed more tophi on DECT scans than clinically apparent. Tendon involvement is much more common than clinically suspected. In contrast to the known bone manifestations (typically "Podagra") we found far more tendon involvement, mainly achilles tendon, than expected. Conclusions: Radiologist and Rheumatologist differed in their results indicating that there might be a learning curve. Further validation is needed to compare the results with other groups to establish a gold standard for interpreting the results of this new technique. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5296